Late Proterozoic unconformity-related hydrothermal iron deposits in the northern Barker area (Tandilia ranges, Argentina) - Dristas, Jorge Anastasio (2007)
New outcrops of hydrothermal clay alterations, associated with the Late Proterozoic unconformity between the migmatitic basement and sedimentary quartzitic sandstone sequence, were found near small iron (goethite and hematite) deposits in the north Barker area (Tandilia, Argentina). Studied rocks from the contact, wall rock deposits and ores give evidence for hydrothermal activity. A characterization of the iron ore genesis, based on petrography, ore microscopy, X-ray diffractometry, fluid inclusion microthermometry, whole rock analyses (major, trace and rare earth elements), cathodoluminescence, and electron microprobe, is given. The iron source may be assigned to the destruction of mafic minerals of the migmatite basement. Aluminium-phosphate- sulphate minerals associated with both altered rocks at the contact, derived from the destruction of apatite and allanite of basement rocks by hydrothermal activity. Preliminary K-Ar dating of secondary well crystallized sericite from basement alteration indicate a Late Precambrian age for the hydrothermal event representing a widely distributed episode at the unconformity between the basement and sedimentary cover in the Tandilia ranges.